3(s-5)-7(4s-7)=

Simple and best practice solution for 3(s-5)-7(4s-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(s-5)-7(4s-7)= equation:


Simplifying
3(s + -5) + -7(4s + -7) = 0

Reorder the terms:
3(-5 + s) + -7(4s + -7) = 0
(-5 * 3 + s * 3) + -7(4s + -7) = 0
(-15 + 3s) + -7(4s + -7) = 0

Reorder the terms:
-15 + 3s + -7(-7 + 4s) = 0
-15 + 3s + (-7 * -7 + 4s * -7) = 0
-15 + 3s + (49 + -28s) = 0

Reorder the terms:
-15 + 49 + 3s + -28s = 0

Combine like terms: -15 + 49 = 34
34 + 3s + -28s = 0

Combine like terms: 3s + -28s = -25s
34 + -25s = 0

Solving
34 + -25s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-34' to each side of the equation.
34 + -34 + -25s = 0 + -34

Combine like terms: 34 + -34 = 0
0 + -25s = 0 + -34
-25s = 0 + -34

Combine like terms: 0 + -34 = -34
-25s = -34

Divide each side by '-25'.
s = 1.36

Simplifying
s = 1.36

See similar equations:

| 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 | | 4(3d-2)=32 |

Equations solver categories